Sales Promotion and Consumer Buying Behavior of FMCG Products In Kathmandu - Lama, Padam Bahadur; Chataut, Mukunda Kumar (Journal of Development Review, 2022)
This study assesses the impact of consumer sales promotion on consumer buying behavior of FMCG products. Consumer buying behavior in the study is a dependent variable and independent variables in the study are buy one get one free, free sample, and price discount. The study is based on primary data accumulated from 297 respondents from general people or consumers who have demonstrated buying behavior. The study is based on cross-sectional data and pursued statistical tests comprising correlation and regression to examine the association and impact of consumer sales promotion on consumer buying behavior of FMCG products. The result shows that the free sample has a negative relationship with consumer buying behavior. It shows that free sample negatively influences consumer buying behavior. Similarly, the price discount is also negatively correlated with consumer buying behavior. It depicts that the higher the discount scheme of the firm, the lower would be the consumer buying behavior. Further, buy one get one free is positively correlated with consumer buying behavior. This study and its results would be helpful for executives of FMCG product companies while making the decision and it also helps to identify the existing preferences of buyers in the market and diagnose the issues exploring better strategy in the organization. Future research can be conducted by adding more research variables of containing more data to examine its impact.